Epigenetics of Notch1 regulation in pulmonary microvascular rarefaction following extrauterine growth restriction. Issue 1 (December 2015) - Tang, Li-Li; Zhang, Li-Yan; Lao, Lin-Jiang; Hu, Qiong-Yao; Gu, Wei-Zhong; Fu, Lin-Chen; Du, Li-Zhong
Abstract Background Extrauterine growth restriction (EUGR) plays an important role in the developmental origin of adult cardiovascular diseases. In an EUGR rat model, we reported an elevated pulmonary arterial pressure in adults and genome-wide epigenetic modifications in pulmonary vascular endothelial cells (PVECs). However, the underlying mechanism of the early nutritional insult that results in pulmonary vascular consequences later in life remains unclear. Methods A rat model was used to investigate the physiological and structural effect of EUGR on early pulmonary vasculature by evaluating right ventricular systolic pressure and pulmonary vascular density in male rats. Epigenetic modifications of the Notch1 gene in PVECs were evaluated. Results EUGR decreased pulmonary vascular density with no significant impact on right ventricular systolic pressure at 3 weeks. Decreased transcription of Notch1 was observed both at 3 and 9 weeks, in association with decreased downstream target gene, Hes-1 . Chromatin immunoprecipitation and bisulfite sequencing were performed to analyze the epigenetic modifications of the Notch1 gene promoter in PVECs. EUGR caused a significantly increased H3K27me3 in the proximal Notch1 gene promoter, and increased methylation of single CpG sites in the distal Notch1 gene promoter, both at 3 and 9 weeks. Conclusions We conclude that EUGR results in decreased pulmonary vascular growth in association with decreased Notch1 in PVECs. This may be mediated by increased CpG methylation and H3K27me3 in the Notch1 gene promoter region.